Comparative gonad transcriptome analysis in cobia (Rachycentron canadum) - Shen, Xueyan; Yáñez, José M.; Bastos Gomes, Giana; Poon, Zhi Weng Josiah; Foster, Derick; Alarcon, Jorge F.; Domingos, Jose A. (Frontiers in Genetics, 2023)
Cobia (Rachycentron canadum) is a species of fish with high commercial potential particularly due to fast growth rates. The evidence of sexual size dimorphism favoring females indicate potential benefits in having a monosex culture. However, the involvement of genetic factors responsible for sexual development and gonadal maintenance that produces phenotypic sex in cobia is largely unknown. In the present study, we performed transcriptome sequencing of cobia to identify sex-biased significantly differentially expressed genes (DEGs) in testes and ovaries. This comparative gonad transcriptomic analysis revealed that 7,120 and 4,628 DEGs are up-regulated in testes or ovaries, respectively. Further functional annotation analyses identified 76 important candidate genes involved in sex determination cascades or sex differentiation, including 42 known testis-biased DEGs (dmrt1, amh and sox9 etc.), and 34 known ovary-biased DEGs (foxl2, sox3 and cyp19a etc.). Moreover, eleven significantly enriched pathways functionally related to sex determination and sex differentiation were identified, including Wnt signalling pathway, oocyte meiosis, the TGF-beta signalling pathway and MAPK signalling pathway. This work represents the first comparative gonad transcriptome study in cobia. The putative sex-associated DEGs and pathways provide an important molecular basis for further investigation of cobia’s sex determination, gonadal development as well as potential control breeding of monosex female populations for a possible aquaculture setting.